1995
DOI: 10.1074/jbc.270.37.21722
|View full text |Cite
|
Sign up to set email alerts
|

Functional Glycosylation Sites of the Rat Luteinizing Hormone Receptor Required for Ligand Binding

Abstract: The contribution of N-linked glycosylation to the ligand binding activity of the rat luteinizing hormone receptor (LHR) was studied in wild-type and mutant LHR expressed in mammalian (COS1) cells and overexpressed in insect (Sf9) cells. The binding affinities of the holoreceptor and its truncated splice variant (form B) lacking the transmembrane domain were equivalent in both cell lines. Tunicamycin-treated transfected Sf9 cells expressed a carbohydrate-free LH receptor that lacked hormone binding activity. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
62
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 20 publications
6
62
0
Order By: Relevance
“…Thus, it was not unexpected that it could be purified by hCG affinity chromatography when expressed in HEK293 cells. This is in line with previous studies that have shown that the variant displays similar high affinity in saturation binding assays as the full-length receptor (Tsai-Morris et al, 1990;Zhang et al, 1995). Nevertheless, because only a very small proportion of the variant was purified and no secretion to the medium was observed, it is apparent that a majority of the protein is not able to find the correct conformation.…”
Section: Discussionsupporting
confidence: 77%
“…Thus, it was not unexpected that it could be purified by hCG affinity chromatography when expressed in HEK293 cells. This is in line with previous studies that have shown that the variant displays similar high affinity in saturation binding assays as the full-length receptor (Tsai-Morris et al, 1990;Zhang et al, 1995). Nevertheless, because only a very small proportion of the variant was purified and no secretion to the medium was observed, it is apparent that a majority of the protein is not able to find the correct conformation.…”
Section: Discussionsupporting
confidence: 77%
“…The LH/hCG receptor is known to contain at least three complex type N-linked oligosaccharide chains (24,25). It is also known that the synthesis of complextype N-linked oligosaccharide chains begins with the cotranslational addition of core mannose rich oligosaccharide chains to the protein.…”
Section: An Autoradiogram Of the [mentioning
confidence: 99%
“…For an extracytoplasmic predicted R-gene product with the LRR motif and the domain being well conserved, there is a possibility that the hydrophobic face can facilitate multiple interactions with other ligands (HammondKosack and Jones, 1997). Zhang et al (1995) have previously shown that the glycosylation pattern within the LRR domain is directly involved in ligand binding. It has been found that the glycosylation sites are generally absent in the β-strand of the LRR region of the C1 domain and so the hydrophobic end plays a role in the interaction, while the glycosylation sites are present within the β-strand of C3 leucine repeats.…”
Section: Leucine-rich Repeatsmentioning
confidence: 99%